Creating a measure to operationalize engaged well-being at work - Bosle, Catherin; Fischer, Joachim E.; Herr, Raphael (Journal of occupational medicine and toxicology, 2021)
Mental well-being and work engagement are both desirable, positive states of mind that help employees to better function in the workplace. While occupational researchers have argued in favor of considering both states concurrently, it is less clear how this might be translated to provide an instrument characterizing the workforce accordingly. The present study describes empirical efforts to operationalize a construct called engaged well-being.
Gesehen am 04.05.2021